Prevalence of SARS-CoV-2 infection in Italian pediatric population: a regional seroepidemiological study - Manola Comar; Simone Benvenuto; Marzia Lazzerini; Giorgio Fedele; Egidio Barbi; Alessandro Amaddeo; Francesco Maria Risso; Tamara Strajn; Paola Di Rocco; Paola Stefanelli; Giovanni Rezza (BMC, 2021)
Abstract Background Data on the effective burden of the SARS-CoV-2 pandemic in pediatric population are very limited, mostly because of the higher rate of asymptomatic or paucisymptomatic cases among children. Updated data on COVID-19 prevalence are needed for their relevance in public health and for infection control policies. In this single-centre cross-sectional study we aimed to assess prevalence of SARS-CoV-2 infection through IgG antibodies detection in an Italian pediatric cohort. Methods The study was conducted in January 2021 among both inpatients and outpatients referring to Research Institute for Maternal and Child Health "Burlo Garofolo" in Trieste, Friuli Venezia-Giulia, Italy, who needed for blood test for any reason. Collected samples were sent to Italian National Institute of Health for analysis through chemiluminescent immunoassay (CLIA). Results One hundred sixty-nine patients were included in the study, with a median age of 10.5 ± 4.1 years, an equal distribution for sex (49.7% female patients), and a 55.6% prevalence of comorbidities. Prevalence of anti-SARS-CoV-2 trimeric Spike protein IgG antibodies was 9.5% (n = 16), with a medium titre of 482.3 ± 387.1 BAU/mL. Having an infected cohabitant strongly correlated with IgG positivity (OR 23.83, 95% CI 7.19-78.98, p < 0.0001), while a cohabitant healthcare worker wasn't associated with a higher risk (OR 1.53, 95% CI 0.4-5.86, p 0.46). All of the 5 patients who had previously tested positive to a nasopharyngeal swab belonged to the IgG positive group, with a 3-month interval from the infection at most. Conclusion We assessed a 9.5% SARS-CoV-2 seroprevalence in a pediatric cohort from Friuli Venezia-Giulia region in January 2021, showing a substantial increase after the second peak of the pandemic occurred starting from October 2020, compared to 1% prevalence observed by National Institute of Statistics (ISTAT) in July 2020.